RELATIONSHIP BETWEEN HYPERTENSION AND THE INCIDENCE OF STROKE IN RSUP PROF. DR. I.G.N.G NGOERAH - Priyatna, Rosabel Eugene; Sinardja, Cyndiana Widia Dewi; Sinardja, Cyndiana Widia Dewi; Artana, I Gusti Ngurah Bagus (E-Jurnal Medika Udayana; Vol 12 No 5 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i05.P07, 2023)
Stroke is a condition that occurs when blood flow to the brain is cut off due to blockage or rupture of blood vessels to the brain, causing brain cell death. Stroke is a disease that has a very high level of morbidity and mortality, especially in Indonesia. Hypertension is one of the main factors of stroke. This study was aimed to determine the relationship of hypertension to the incidence of stroke in RSUP Prof. Dr. I.G.N.G Ngoerah. This study used a cross-sectional analytic observational study design on 150 stroke patients at RSUP Prof. Dr. I.G.N.G Ngoerah in the period June 2021-June 2022. This study shows the proportion of non-hemorrhagic stroke is 56.7% and hemorrhagic stroke is 43.3%; stroke patients who have hypertension by 72.7%; stroke was more common in patients aged ?58 years with a proportion of 52%; and stroke was more common in male patients with a proportion of 63.3%. For the non-parametric correlation value of hypertension with non-hemorrhagic stroke and hemorrhagic stroke found r = 0.265 with p value = 0.001; p <0.05. This value indicates a weak positive relationship between hypertension to the incidence of non-hemorrhagic stroke and hemorrhagic stroke which proved significant. This is due to hypertension causing endothelial dysfunction so that it can trigger the formation of arterosclerosis and/or rupture of blood vessels. Preventive measures to maintain blood pressure play an important role in preventing complications of stroke.